2013
DOI: 10.1177/0893318912469771
|View full text |Cite
|
Sign up to set email alerts
|

Communicating During Organizational Change Using Social Accounts

Abstract: One way to improve trust in management during large-scale organization changes is with effective communications. This article looks at three types of social accounts (causal, ideological, and referential accounts) to see which are effective at improving trust during major organizational changes. A field study method explored two organizations and found that ideological accounts were best at improving trust in management. The relationship between ideological accounts and trust was mediated by the success of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…They worked hard to ensure that their decisions were well (Cameron and Quinn, 2006) and that consistency between the organization's vision and explanations of the transformation are important for building trust and creating commitment to change (Tucker et al, 2013b). Also related to this is the notion that the changes at Arlington were viewed as an extension of already changing values and beliefs within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…They worked hard to ensure that their decisions were well (Cameron and Quinn, 2006) and that consistency between the organization's vision and explanations of the transformation are important for building trust and creating commitment to change (Tucker et al, 2013b). Also related to this is the notion that the changes at Arlington were viewed as an extension of already changing values and beliefs within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Сегодня для легитимизации принятых решений эксперты выдвигают такую по следовательность действий: «менеджмент -ценности -коммуникация» [Tucker, Yeow, Viki, 2013], при этом коммуникация становится основным инструментом принятого решения. Однако необходимо также выстроить следующую коммуника тивную триаду месседжа: «основная идея -изобразительный ряд -лексическое наполнение».…”
Section: заключение и перспективы исследованияunclassified
“…We only found two social account studies which actively sought to consider the recipient's interpretation. Tucker et al (2013) measure the impact of the perceived content of accounts -rather than their intended design -on trust in management, whilst Van Dijke and De Cremer (2011) found that the recipient's stress responses to uncertainty had a moderating effect on effectiveness.…”
Section: Interpretation Of Social Accountsmentioning
confidence: 99%
“…Although, originally focused on dyadic explanations, recent research has considered the accounts of individuals, as representatives, who explain the actions of the organization to others (for example, the announcement of a merger (e.g. Tucker et al, 2013), or downsizing (e.g. Brockner, Dewitt, Grover, & Reed, 1990.…”
Section: Interpretation Of Social Accountsmentioning
confidence: 99%
See 1 more Smart Citation